Pago con acciones liberadas influye en la capacidad económica de los accionistas minoritarios - Torre Padilla, Abdias Armando (2023)
This study examines how the payment of dividends through freed-up shares by companies listed on the Bolsa de Valores de Lima (BVL) during the period 2009-2016 has negatively affected the economic capacity of minority shareholders. The dividend policy adopted by these companies has caused economic harm due to the distribution of freed-up shares instead of cash dividends. The shareholders’ concern is justified as they expect a cash return on their investment, as dividends are considered their natural source of income. This provides them with immediate access to cash when needed, whereas receiving freed-up shares does not. To avoid further damage to the economic capacity of minority shareholders, the solution is to shift the dividend policy model from distributing freed-up shares to paying dividends in cash. The evidence gathered in this study provides information on the distribution of freed-up shares to shareholders, and the analysis conducted through indicators can be used as a model. Ultimately, the study concludes that the payment of dividends through freed-up shares has a negative impact on the economic capacity of minority shareholders.